Implementation of the Social Assistance Budget in Achieving Poverty Alleviation Performance in East Kutai Regency - Siti Neza Aulia; Cornelius Rante Langi; Wulan Iyhig Ratna Sari (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the implementation of social assistance budget and its relationship with the achievement of poverty alleviation performance in East Kutai Regency. The focus of the study is the performance of the implementation of the social assistance budget in supporting the reduction of poverty indicators. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. Data on the distribution of social assistance budget and data on aid recipients. Research informants consist of implementing officials, data operators and field assistants involved in the verification and distribution process of aid. Data analysis was carried out by referring to the qualitative analysis stages. The findings were analyzed based on the Theory of Change framework to see the relationship between problems, activities, outputs, outcomes, and desired states (impacts). The results of the study indicate that the implementation of the social assistance budget in general has had an impact on the achievement of poverty reduction in East Kutai. This can be seen from in the percentage of poor people from 9.28% (2022), to 9.06% (2023) to 8.81% (2024). However, the social assistance budget has not been fully able to reduce poverty problems and rates. This finding is an important basis for local governments in designing more adaptive and sustainable poverty alleviation strategies.